Odpowiedzi

2009-12-15T21:03:15+01:00
A.
2x + y = 9
5x - 4y = 3

y = 9 - 2x
5x - 4( 9 - 2x) = 3

y = 9 - 2x
5x - 36 + 8x = 3

y = 9 - 2x
13x = 3 + 36

y = 9 - 2x
13x = 39 /:13

y = 9 - 2x
x = 3

y = 9 - 2 (razy) 3
x = 3

y = 3
x = 3

b.
3x - 2y = 5
2x - y = 4

3x - 2y = 5
-y = 4 - 2x / (razy) (-1)

3x - 2y = 5
y = -4 +2x

3x - 2(-4 + 2x) = 5
y = -4 + 2x

3x + 8 - 4x = 5
y = -4 + 2x

-x = -3 / :(-1)
y = -4 + 2x

x = 3
y = -4 + 2 (razy) 3

x = 3
y = 2

c.
2x+9y=-9
-3x+3y=8

2x = -9 -9y /:2
-3x + 3y = 8

x = - 4,5 - 4,5y
-3 (-4,5 - 4,5y) + 3y = 8

x = -4,5 -4,5y
13,5 + 13,5y +3y = 8

x = - 4,5 - 4,5y
16,5y = -5,5 /: 16,5

x = - 4,5 - 4,5y
y = (jedna trzecia)

x = - 4,5 - 4,5 (razy jedna trzecia)
y = jedna trzecia

x = - 4,5 - 1,5
y = jedna trzecia

x = 6
y = jedna trzecia

d.
2x+3y=4
8x-5y=-1

2x = 4 - 3y /: 2
8x - 5y = -1

X = 2 - (trzy drugie)y
8 ( 2 - (trzy drugie)y ) - 5y = -1

X = 2 - (trzy drugie)y
16 - 12y - 5y = -1

X = 2 - (trzy drugie)y
-17y = -17 /: (-17)

X = 2 - (trzy drugie)y
y = 1

X = 2 - (trzy drugie) 1
y = 1

x = 0,5
y = 1

h.
x-y=0
x+y+z=4
x+2y+3z=9

x = y
x + y + z = 4
x + 2x + 3z = 9

x = y
x + y + z = 4
3x = 9 - 3z /:3

x = y
x + y + z = 4
x = 3 - z

x = y
3 - z + 3 - z + z = 4
x = 3 - z

x = y
-z = -2 /:(-1)
x = 3 - z

x = y
z = 2
x = 3 - 2

x = y
z = 2
x = 1

( x (z) y są sobie równe więc mają wartość 1)

czyli napisz tak:
y = 1
z = 2
x = 1